Pengaruh Pembelajaran Aktif Berbantuan Media Bonus (Boneka Nusantara) Terhadap Hasil Belajar IPS - Yuka Rahmah Tiara Cahya (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the active learning model assisted bythe BONUS (Boneka Nusantara) media on social studies learning outcomes for fourthgrade students at SD N Sukorejo Magelang.This research is a type of experimental research with Pre-experimentalresearch design with the "One Group Pretest-Posttest Design" model. The researchsubjects are 10 fourth grade students of SD N Sukorejo in Ganjuran Village whichconsists of 10 female students as the experimental class. The sampling technique usedwas saturated purposive sampling technique. The data collection technique usedpretest and posttest questions regarding ethnic and cultural diversity and observation.Data analysis in this study was assisted by using SPSS version 25 to calculate thevalidity, reliability, discriminating power, and level of difficulty of the questions.Validity test using product moment correlation and instrument reliability using Cronboach's Alpha. The data analysis technique in this study uses the Kolmogorov-Smirnov analysis prerequisite test and the hypothesis test uses the Paired Sample T-Test. The results showed that the active learning model assisted by the Nusantaradoll media had a positive effect on student learning outcomes. This is evidenced fromthe results of the analysis of the Paired Sample T-Test in the experimental group witha sig (2-tailed) value of 0.000 <0.05 and the result of tcount 7.488 > 2,228 ttable . Basedon the results of the analysis and discussion, there is a difference in the pretest score of60 and the posttest of 78. The results of the study can be concluded that the use of activelearning aided by the Nusantara doll media has a positive effect on the learningoutcomes of fourth grade students of SD N Sukorejo.